Generation of high pressures by short-pulse low-energy laser irradiation. (24th October 2017) - Jakubowska, K.; Batani, D.; Feugeas, J.-F.; Forestier-Colleoni, P.; Hulin, S.; Nicolaï, P.; Santos, J. J.; Flacco, A.; Vauzour, B.; Malka, V.
Abstract: The goal of this paper is twofold: first, we demonstrate shock generation with ultra-short (24 fs) and low-energy (J) laser pulse, following the energy deposition in the target by fast electrons; second, we show that such shocks can be used to provide information on compressed matter. For a target with thickness we have clearly inferred the formation of a shock wave with pressure . We have also measured the color temperature of the emitting target rear side at breakout time, which is in good agreement with predictions from equation-of-state models (SESAME tables) and hydrodynamic simulations.